Influence of fossoriality on inner ear morphology: insights from caecilian amphibians - Maddin, Hillary C (Blackwell Science Inc, 2014)
It is widely accepted that a relationship exists between inner ear morphology and functional aspects of an animal's biology, such as locomotor behaviour. Animals that engage in agile and spatially complex behaviours possess semicircular canals that morphologically maximise sensitivity to correspondingly complex physical stimuli. Stemming from the prediction that fossorial tetrapods require a well-developed sense of spatial awareness, we investigate the hypothesis that fossoriality leads to inner ear morphology that is convergent with other spatially adept tetrapods. We apply morphometrics to otic capsule endocasts of 26 caecilian species to quantify aspects of inner ear shape, and compare these with a sample of frog and salamander species. Our results reveal caecilians (and also frogs) possess strongly curved canals, a feature in common with spatially adept species. However, significantly shorter canals in caecilians suggest reduced sensitivity, possibly associated with reduced reliance on vestibulo-ocular reflexes in this group of visually degenerate tetrapods. An elaboration of the sacculus of caecilians is interpreted as a unique adaptation among amphibians to increase sensitivity to substrate-borne vibrations transmitted through the head. This study represents the first quantitative analyses of inner ear morphology of limbless fossorial tetrapods, and identifies features within a new behavioural context that will contribute to our understanding of the biological consequences of physical stimuli on sensory function and associated morphological evolution.